Experience With Polymer Thick Film Technology. (1983) - Hulkkonen, Raimo; Jarvinen, Eero; Sortti, Vesa
Abstract : The paper describes a user's experiences with polymer thick film resistor technology. The characteristics studied are resistance values and their distributing. Parameters affecting these characteristics are the material of the substrate, and the curing of the polymer resistor paste. The test conditions (temperature cycling, dip soldering, high temperature storaging) were chosen to simulate the environmental conditions, through which the polymer resistor circuits have to go during the assembly process of a typical consumer electronics product. The polymer pastes studied were from commercial paste manufacturers in USA, Europe and Japan. Additional background information, to help in understanding the behaviour of different polymer resistor materials, was obtained through the differential thermo analysis (DTA) of the pastes under investigation.